STRESS ANALYSIS OF REDUCED BEAM SECTION STEEL MOMENT CONNECTION (AISC 358-2005) - KUKUH KURNIAWAN DWI SUNGKONO (Fakultas Teknik Universitas Tunas Pembangunan Surakarta, 2017)
Earthquakeresistant building structures should be properly andappropriately designed, especially in the planning and detailing of the beam - column connections. Thecollapse mechanism of seismic building shall occur plastichinge first and the column is still in elastic condition (strong column weak beam).AISC 358-2005 provides type of steel connection for seismic buialding. In the regulation mentioned that the connection is used in the structure with the Special Moment Frames (SMF) and Intermediate Moment Frames (IMF), one of the connection types is reduced beam section. Reduced Beam Section (RBS) moment connection, portionsof the beam flangesare selectively trimmed in the region adjacent to the beamtocolumn connection. Result modeling RBS on FEM, the top of the beam occur tensile strenght 1367kN/m2, the bottom of the beam has a compressive stress 2943kN/m2, the beam web has a tensile stress 1281kN/m2, the face of the column occur tensile stress 667kN/m2 and the column web 857kN/m2. The shear stress in the beam web is largest (857kN/m2) than on the beam flange (275kN/m2), and the shear stress on the column is smaller (503kN/m2).